Associations of mode and distance of commuting to school with cardiorespiratory fitness in Slovenian schoolchildren: a nationwide cross-sectional study - Gregor Jurak; Maroje Soric; Vedrana Sember; Sasa Djuric; Gregor Starc; Marjeta Kovac; Bojan Leskosek (BMC, 2021)
Abstract Background It is unclear whether active commuting has the potential to improve children's health. This study examined the association of commuting mode and distance with children's cardiorespiratory fitness (CRF). Methods We conducted a cross-sectional study, including 713 Slovenian schoolchildren aged 12 to 15 years. Commuting modes were self-reported, and four commuting groups were constructed, while CRF was determined with a 20-m shuttle run test. The distance from home to school was calculated using the Geographic Information System. Effects of commuting mode and distance, controlling for age, gender and amount of total physical activity, were evaluated using general two linear models (one for each direction of commuting to/from school). Results The main effect of commuting group on CRF and its interaction with distance were significant in the direction from school to home (P = 0.013 and P = 0.028, respectively), but not in the opposite direction. Predicted differences in CRF between commuting groups were moderate and generally higher in males than in females. When comparing commuting group median distance from home to school, males driven by car had around 4 ml/min/kg lower predicted CRF than those who walked (P = 0.01) or used wheels commuting (e.g., bicycle, skateboard). Conclusions The distance of commuting had a small effect on CRF, except in the Car group where children who live close to school had significantly lower CRF than those living further away. Children driven by car who live within wheels or walk distance from school should be targeted by interventions promoting active transport.